Exercise interventions for mental disorders in young people: a scoping review - Alan P Bailey; Melinda Craike; Tim Carter; Rhiannon Patten; Michaela C Pascoe; Nigel K Stepto; Alexandra G Parker (BMJ Open Sport & Exercise Medicine, 2020)
Aims This scoping review determines the breadth and outcomes of controlled trials testing the effect of physical activity/exercise interventions across mental health outcomes in young people with a mental disorder.Methods The literature search was conducted using the open-access ‘Evidence Finder’, a comprehensive youth mental health-specific database that is systematically populated from MEDLINE, Embase, PsycINFO and Cochrane CENTRAL databases.Results Sixteen publications were identified after meeting the following eligibility criteria: (1) participants were young people (mean age 12–25.9 years) with a mental disorder diagnosed by a trained clinician or by reaching a predefined cut score on a symptom measure, (2) interventions were exercise, (3) designs were randomised or non-randomised controlled trials, (4) outcomes were mental health related. Eight studies included young people with depression, three included people with psychosis/schizophrenia, three included people with eating disorders and two included people with anxiety. The available evidence suggests that moderate-to-vigorous-intensity exercise may be beneficial, particularly for reducing depression. The available evidence for other intervention intensities, and for other mental disorders, is mixed.Conclusions Overall, the evidence regarding the impact of exercise interventions on a range of mental health outcomes in clinical populations of young people with various mental disorders looks promising but requires further development. Findings from this scoping review can inform the development of future exercise interventions in the youth mental health field.